Why Sprawl is a Problem: Interview with Evan Richert - Richert, Evan; Lachance, Laurie (Maine Policy Review, 1997)
A recent report of the Maine State Planning Office entitled "The Cost of Sprawl" (May 1997) begins with the observation.... "We are spreading out. Over the last 30 years, the fastest growing towns in Maine have been "new suburbs" 10 to 25 miles distant from metropolitan areas....These high growth communities have accounted for virtually all of the state's population growth. From town square to the countryside, from Main Street to the mall, we are dispersing.... This outward movement has had unanticipated and unintended consequences...." Such consequences are the focus of this interview with Evan Richert, director of the Maine State Planning Office. Richert points out that sprawl has implications for Maine's fiscal integrity, quality of environment, and character of communities. As policymakers continue to focus on reducing tax burden and promoting economic development, Richert points out that the issue of sprawl will need to be factored into our solutions. He calls for statewide dialogue and suggests pursuing economic incentives rather than a regulatory approach to curb this pattern of development. Richert also comments on the status of utility restructuring. He is joined by State Economist Laurie Lachance for this portion of the interview.
Keywords: Maine land-use patterns; sprawl